2015
DOI: 10.1111/jam.12858
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness and recombination analysis ofAllorhizobium vitisstrains associated with grapevine crown gall outbreaks in Europe

Abstract: We demonstrated clear epidemiological relationship between majority of strains studied, suggesting a need for more stringent phytosanitary measures in international trade. Moreover, this is the first study to report recombination in A. vitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…vitis strains used in this study were isolated from crown gall tumors on grapevine originating from different geographical areas (Table 1). These strains were predominantly representatives of the two main phylogenetic groups (C and D) delineated in our previous study (Kuzmanovid et al, 2015).…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations
“…vitis strains used in this study were isolated from crown gall tumors on grapevine originating from different geographical areas (Table 1). These strains were predominantly representatives of the two main phylogenetic groups (C and D) delineated in our previous study (Kuzmanovid et al, 2015).…”
Section: Methodsmentioning
confidence: 79%
“…Our previous study based on the analysis of several housekeeping gene sequences suggested the existence of several phylogenetic groups within All. vitis species complex (Kuzmanovid et al, 2015). The present study focused on two phylogenetic groups defined in the previous study, the first comprises the type strain of All.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…vitis harboured a circular chromid, supporting the distinction into different genera (Ram ırez-Bahena et al 2014). In the same way, recent phylogenetic and genomic analyses proposed that Agrobacterium must be retained as a valid genus gathering Agrobacterium rubi, Agrobacterium larrymoorei and agrobacteria of the so-called biovar 1 (Ram ırez-Bahena et al 2014;Kuzmanovi c et al 2015;Mousavi et al 2015). The appellation 'biovar 1' comprises several genomic species (or genomospecies), called G1 to G9, G13 and G14, among which some received a Latin epithet, such as 'Agrobacterium fabrum' for G8 (Lassalle et al 2011;Shams et al 2013).…”
Section: Introductionmentioning
confidence: 99%